An Investigation of the Enolization and Isomeric Products Distribution in the Water Promoted Aldol Reaction of Tropinone and Granatanone - Ryszard Lazny; Artur Ratkiewicz; Krzysztof Brzezinski; Aneta Nodzewska; Katarzyna Sidorowicz (Journal of Chemistry)
The exo,anti/exo,syn-diastereoselectivity of water promoted direct aldol reactions of tropinone and granatanone (pseudopelletierine) is strongly dependent on the amount of water added and aromatic aldehyde used. DFT methods were applied to calculate the free energies of tropinone and granatanone enols, transition states, and isomeric aldol products. A theoretical model was verified by comparison of results from several DFT methods and functionals with experiments. The 6-31g(d)/CPCM method proved most suited to the problem, although all methods tested predicted similar trends. Explicit inclusion of a water molecule bonded to the amino ketones resulted in increased stability of the enol forms. The dependence of the anti/syn-diastereoselectivity on the amount of water used may be rationalized on the basis of change in the polarity of the reaction medium. The predicted stabilities of competing products agreed with experimental results supporting the notion of thermodynamic control. The isomeric products distributions for the aldol reaction of several aromatic aldehydes in solventless (neat) conditions were accurately calculated from free energies of the aldol addition step in the gas phase using B3LYP/6-31g(d) method and in aqueous conditions using the CPCM-B3LYP/6-31g(d) model. Our methodology can be useful for predicting the outcome of this type of aldol reactions.